Effect of flooding in critical stage on cadmium accumulation and translocation of rice in different paddy soils - ZOU Wenxian; ZHOU Yuning; GU Siting; HUANG Tuhai; ZHI Yuyou; MENG Long; SHI Jiachun; CHEN Jian; XU Jianming (浙江大学学报. 农业与生命科学版, 2021)
A pot experiment was conducted in two paddy soils [paddy field on desalting clayey polder soil (PC) and diluvial gritty loaming paddy soil (DP)] to explore the effects of critical stage moisture managements on cadmium (Cd) accumulation and translocation in rice with five water managements. The water managements were moisture throughout growth (CK), continuous flooding (YS), flooding at tillering-jointing stage (FB), flooding at heading stage (CS) and flooding at filling-maturing stage (GC). The results showed that, in tillering stage, the contents of soil exchangeable Cd were CK≈CS≈GC≫FB≈YS, and in other rice growth stages, which were CK≈FB≈CS≈GC≫YS. In PC, Cd contents in grain were FB＞GC≈CK＞CS＞YS, and Cd content in grain of CS treatment decreased by 49.99% as compared with the CK. In DP, Cd contents in grain were CK≈GC＞CS≈FB＞YS, and Cd contents in grain of FB and CS treatments decreased by 50.52% and 44.85%, respectively, when compared with the CK. In PC, when compared with the CK treatment, CS treatment decreased the Cd translocation factor from stem to grain (TF2), but FB treatment increased it. In DP, both FB and CS treatments reduced TF2, when compared with the CK. There was a positive correlation between Cd content in grain and Cd content on root surface, and FB and CS treatments decreased the Cd contents on root surface in both paddy soils. FB treatment significantly increased the dithion-citrate-bicarbonate (DCB)-Fe content compared with other treatments in both paddy soils. The Cd content in grain had significant (P＜0.05) and highly significant (P＜0.01) negative correlation relationships with DCB-Fe and DCB-Mn in DP, but the relationship was not observed in PC. In summary, flooding measures in different stages influence the Cd content in grain by affecting the Cd translocation from stem to grain and affecting Cd content on root surface. Heading stage is the critical flooding stage in PC. In DP, tillering-jointing and heading stages are the critical flooding stages. The iron plaque has different effects on grain Cd accumulation and translocation in different paddy soils, which resulting in different critical flooding stages in two paddy soils.